VOCATIONAL SKILL SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH LUAR BIASA - Istiqomah, Nurul (Jurnal Pendidikan Khusus, 2017)
Abstrack : The limitedness carried by the special need children had impact to their autonomous in social life one of them was related with an occupation. The occupation should be needed in the society but the special need children with limited ability could not do the job appropriate with the needs in the society yet. The purpose of this research was to describe the teacher’s knowledge about vocational skill, vocational skill program, instrument and media in the activity of vocational skill, the implementation of vocational skill, the problem in the activity of vocational skill, and the solution in the activity of vocational skill in special school. This research used qualitative kind of descriptive study. The subjects of this research were two special schools in Surabaya. The data collection technique applied was interview, observation, and documentation. The technique of data analysis used was in the form of data condensation, data display, and conclusion drawing / verification. The research result could be obtained by the counselor teachers of vocational skill to percept that vocational skill was a skill or learning given to special need student to make them being autonomous in the future by training the student’s motoric so that it could be perfect. The kinds of vocational skill implemented was food science, skill, cleaning service, laundry, washing motorcycle, music art, dance art, sport, IT KMD, printing, entrepreneurship, and sewing. Making the program of vocational skill activity was done by the counselor teacher of vocational skill. The instrument and media used in this vocational skill activity was directly adjusted to vocational skill activity. The implementation of vocational skill activity was begun by arising the student’s interest to follow vocational skill activity and to divide the students into several groups. The problem experienced by the school was financial and special need children’s behavior. The problem could be solved by the teacher him/herself and conditioning the students before following the vocational skill activity. Keywords: vocational skill, special need students